Protective effects of St. John's wort in the hepatic ischemia/reperfusion injury in rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; ERZİK, CAN; ÖZKAN YENAL, NAZİYE; ÇETİNEL, ŞULE (AVES, 2018)
Objectives: The purpose of this study was to investigate possible protective effects of St. John's wort in the hepatic ischemia/reperfusion injury. Material and Methods: The hepatic artery, portal vein, and bile duct were all clamped for 45 minutes to induce ischemia in rats, and after that reperfusion for 1 hour. SJW was administrated orally, once a day for 3 days before ischemia/reperfusion. The aspartate aminotransferase, alanine aminotransferase, tumor necrosis factor, and interleukin levels were measured in the serum samples. Luminol chemiluminescence, lucigenin luminol chemiluminescence levels; myeloperoxidase. The sodium-potassium ATPase (Na+/K+ ATPase) activity was determined in the liver tissue, and caspase-3 and caspase-9 activity with the bcl-2/bax ratio were measured by the western blot analysis. Results: The St. John's wort administration recovered the aspartate aminotransferase, alanine aminotransferase, tumor necrosis factor, and IL-1 beta levels serum parameters meaningfully, while ischemia/reperfusion caused an increase in luminol chemiluminescence, lucigenin luminol chemiluminescence, myeloperoxidase, caspase-3, and caspase-9 activity and led to a decrease in the B-cell lymphoma-2/bcl-2-associated X protein (bcl-2/bax) ratio and the Na+/K+ ATPase activity. Conclusion: The obtained results indicate protective effects of St. John's wort on the ischemia/reperfusion injury through various mechanisms, and we are able to suggest that St. John's wort can clinically create a new therapeutic principle.
Keywords: Apoptosis; inflammatory; ischemia/reperfusion; St. John's wort; ISCHEMIA-REPERFUSION INJURY; HEPATECTOMY; INDUCTION; MICE